Cinta Tanah Air di Era Global - Tridiatno, Yoachim Agus; Suryanti, Chatarina (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the meaning of love for the homeland from time to time, the concept of world citizenship, global citizenship, and cosmopolitanism in the global era, and analyze the urgency of patriotism education in the global era. This study used a qualitative method by explaining the feelings and ideas of the informants regarding the occurrence of a specific behaviour or symptom. The meaning of love for the homeland had shifted from ancient times, medieval times, to modern times. In ancient times, love for the homeland was regional; in the Middle Ages, it was personal; while in modern times, it was more national and national. The concepts of global citizenship, global citizenship, and cosmopolitanism in the global era showed connectivity and interdependence between humans in all parts of the world. The urgency of patriotism education in the global era was related to providing learning materials about global citizenship education or global citizenship education to instil awareness of universal humanitarian issues.